Nepali Migrant Workers in Tourism Sector of India: A Case in Kerala and Goa (Patan Pragya, 2020)
This paper examines how tourism employment and workplace experiences influence migrant workers' adaptation in the host society. Nepali migration to India is age-old phenomena. Most of literatures depicts to Nepali migrants in India are low-skilled, manual labourers. It is argued that tourism employment provides access to multiple social networks, which subsequently supports the improvement of foreign workers’ social and cultural competencies. Such networks also help to compensate for the negative aspects of migrants and migration. Contrary of negative portraying, it resulted that Nepali migrants in tourism sector of India are in better off position. In addition, the paper considers how relationships among international workers inform chain migration and influence subsequent recruitment practices and migration experiences. The findings stem from study of the experiences of Nepali migrant workers employed in the India tourism sector using qualitative data.